Peran Media Massa dalam Menyampaikan Informasi Pemilu 2019 di Kabupaten Tanjung Jabung Timur - Edi Dwi Abimayu; Muhaimin; Sururuddin; M. Junaidi (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
The limited access to mass media dissemination in East Tanjab and the lack of public awareness in accessing mass media are the background of this research. The purpose of the study discusses the role of mass media in conveying information on the 2019 election, how KPUD uses mass media in conveying information on the 2019 election, what media is used and what information is conveyed and what obstacles and obstacles occur. The method used is descriptive qualitative method, that is, this research is defined as an attempt to find the truth of phenomena, facts, or all symptoms in a scientific way to solve problems or develop science. The research approach used is case studies, including descriptive analysis research. The data analysis methods used were domain analysis and textonomy analysis, while the data validity methods used included extension of participation, persistence of observations and discussions with colleagues. The conclusion of this study is the dissemination of election information carried out by the KPU using various mass media and forming democratic volunteers whose aim is to improve the quality of elections, voter participation, and public confidence in the democratic process carried out in the Tanjung Jabung Timur Regency.